TOPENG BALI SEBAGAI SUMBER INSPIRASI IDE DALAM PENCIPTAAN KARYA SENI LUKIS - Putra, I Gusti Made Dwi Suantara; Gulendra, I Wayan; Utami, Ni Made Purnami (Program Studi Seni Murni ISI Bali, 2025)
Mask art is one of the cultural arts products of the Indonesian people that we still encounter a lot. In various regions, masks have different roles and functions because each region has different customs and beliefs. Apart from being associated with dance, Balinese masks are also often used in theatrical performances or a combination of dance and theater, because Balinese masks themselves have many different characters. Balinese masks themselves have many meanings of life in them which the author then packages into a work of painting which contains messages and knowledge that can broaden insight for a wide audience. The creation method used is a method of creation by creating works of painting in a systematic way. The stages of creating a work of painting which outlines the design of the process of creating a work of art according to the stages of creation from getting the inspiration (idea), designing, to realizing the work of art is a creation method developed by Hawkins. The author chose Balinese masks as an idea for creating this painting because Balinese masks themselves have many different characters, Balinese masks themselves have many meanings of life in them. Which is then packaged by the author into a work of fine art containing messages and knowledge that can broaden insight for a wide audience. This makes the author create paintings using masks as objects combined with the shape of the human body to support the creation of inspirational ideas.